Evaluation of Athletic Extracurricular Programs: Program Evaluation Research on MAN Insan Scholar Serpong Students, National Leading School, Ministry of Religion of the Republic of Indonesia Batch 28, 2023 - Muslih, Muslih; Supriadi, Dedi; Ishak, Muchamad; Sobarna, Akhmad (International Journal of Business, Law, and Education, 2024)
The research evaluates the Extracurricular Athletic Program for Class 28 of 2023 students at MAN Insan Scholar Serpong using the CIPP model, focusing on context, input, process, and product dimensions. The study finds compatibility between program goals and the institution’s vision and mission. Legal basis and needs analysis align with program objectives. Input planning is thorough but requires optimization. Human resources and support from the institution are adequate, though facility quantity needs improvement. The process implementation, including training, competitions, and monitoring, meets standards. Overall, the Program contributes to students’ physical abilities, attitudes, behavior, knowledge, skills, and academic achievements, demonstrating significant improvement compared to previous years.